Brazilian Peppertree Control - Kenneth Gioeli; Stephen Enloe; Carey Minteer; Deah Lieurance; Kenneth Langeland (EDIS)
This publication presents management recommendations for the Brazilian peppertree. It contains information about Brazilian peppertree biology, herbicide application techniques, and the status of biological control. Written by K. T. Gioeli, S. F. Enloe, C. R. Minteer, D. M. Lieurance, and K. A. Langeland, and published by the UF/IFAS Agronomy Department, revised November 2021.